Sustainable energy for all : a framework for action (UN New YorkUS, 2012)
Presents information on the launching of the UN Secretary-General's High-level Group on Sustainable Energy For All which will seek to achieve three critical objectives by 2030 viz, ensuring universal access to modern energy services, doubling the global rate of improvement in energy efficiency and doubling the share of renewable energy in the global energy mix.
Keywords: ENERGY